Mega creativing 5 langkah berpikir jenius Andrei G. Aleinikov ; penerjemah, Alta Virin, Anton Kurnia ; editor, mathori A. Elwa - ALEINIKOV, Andrei G; Veri, Alta; Kurnia, Anton; Elwa, Mathori A (Nuansa, 2005)
224 hlm ilus 24 cm